The Influence of Training and Motivation on Employee Performance at the Regional Development Planning Agency of Bengkulu Province - Stepan Surya Jaya; Nasution Nasution (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to investigate the impact of training and motivation on staff performance at Bengkulu Province's Regional Development Planning Agency (Bappeda). A questionnaire was utilized as a data gathering tool in the survey research approach. The research population consisted of 106 Bappeda employees from Bengkulu Province. Purposive sampling was used to choose the research sample of 80 persons. Multiple linear regression analysis was utilized to analyze the data with the SPSS version 12 application. According to the findings of the study, employee performance is highly influenced by both training and motivation. Training and motivation both have a good and substantial influence on employee performance.